The Main Principles of Ibn Khaldun's Thoughts in the Formation of Islamic Education - Muhtadi Abdul Mun’im; Uswatun Hasanah (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This study aims to determine the Principles of Thought of Ibn Khaldun about the conception of Islamic Education. The research method used is a literature study with support from several sources such as journals, books, articles and other research results which are then analyzed to find a conclusion. The results showed that education according to Ibn Khaldun is not just a means to gain knowledge, but education is also an important medium in the formation of students' character, skills, and readiness in the world of work. Ibn Khaldun also divides the objectives of Islamic education into the formation of good thinking and the improvement of a decent life for the community and the growth of faith values. With this approach, education is expected to be able to produce individuals who can make a positive contribution to society and achieve a better quality of life